Demand-Side Stabilization Policies : What is the Evidence of their Potential? - Kandil, Magda (IMF Working Papers; Working Paper ;, 2000)
Using disaggregated data for the United States, this paper explores the effects of the variability of fiscal and monetary policy shocks. Higher variability of government spending shocks around a steady-state growth trend results, on average, in a decline in aggregate demand growth and inflation, with limited effects on output growth. On the other hand, higher variability of monetary shocks results, on average, in an increase in inflation and a decline in output growth. These results indicate the desirability of avoiding large fluctuations over time in either government spending or the money supply.